2020
DOI: 10.1029/2020gb006559
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Dominated Long‐Term Soil Carbon Losses of Inner Mongolian Grasslands

Abstract: Soil organic carbon (SOC) is the most critical component of global carbon cycle in grassland ecosystems. There has been growing interest in understanding SOC dynamics and driving forces of grassland biomes at various temporal and spatial scales. Up to now, estimates of long-term and large-scale changes in SOC of grassland biomes have been mostly based on modeling approaches and manipulative experiments, rather than direct measurements. During 2007-2011, we repeated 141 soil profiles of the sampling in 1963-196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…In this context, long-term surveys can be extremely valuable. For example, a recent study in Chinese grasslands was able to detect warming-induced soil C losses since the 1960s and, consistent with the global analysis presented here, coarsertextured soils lost far greater amounts of SOM 28 . Experimental soil warming studies also offer opportunities for further determining the factors controlling soil C storage and predicting rates of C release, although recent syntheses have produced conflicting overall findings 29,30 .…”
Section: Resultssupporting
confidence: 88%
“…In this context, long-term surveys can be extremely valuable. For example, a recent study in Chinese grasslands was able to detect warming-induced soil C losses since the 1960s and, consistent with the global analysis presented here, coarsertextured soils lost far greater amounts of SOM 28 . Experimental soil warming studies also offer opportunities for further determining the factors controlling soil C storage and predicting rates of C release, although recent syntheses have produced conflicting overall findings 29,30 .…”
Section: Resultssupporting
confidence: 88%
“…Soil organic carbon plays an extremely important role in the global carbon cycle process [ 48 ]. Xin et al found that organic carbon in 0–100 cm soil was lost at a rate of 48.4 Tg C year −1 between 1963 and 2007 [ 49 ]. There is a significant positive correlation between plant root traits (root biomass, underground plant carbon, nitrogen, and phosphorus content) and microbial residual carbon [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Karst desertification, which is similar to desertified landscapes, has attracted much attention from the international community (Xiong et al, 2002 ). It has been shown that the establishment of artificial grasslands is an important initiative to rapidly repair the damaged ecological environment of rocky desertification (Wang et al, 2019 ), which is of great significance to promote ecological reconstruction and economic development (Fang et al, 2018 ; Xin et al, 2020 ; Bai and Cotrufo, 2022 ). However, due to the different utilization of artificial grassland, desertification may change the microbial community structure formed by long-term evolution and then change the soil microbial–soil–plant nutrient relationship (Pei et al, 2021 ), ultimately having a profound effect on grassland ecosystems and their functions (Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%